Exploiting performance gap among two users in reconfigurable intelligent surfaces-aided wireless systems - Dinh-Thuan Do; Chi-Bao Le (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
In this work, we study the outage performance of a reconfigurable intelligent surfaces (RIS)-aided wireless systems in the presence of non-orthogonal multiple access (NOMA). In particular, different power factors are allocated to users which belong a dedicated group. We derive exact outage probability of two users in a group. Specifically, it is assumed that the RIS is placed between the source and the users and far user has better performance under assistance of RIS. We also provide comparison analysis to investigate the effect of the main parameters on the outage performance of our proposed system, such as the number of tunable elements of the RIS, power allocation factors, target rates and the average signal-to-noise ratio at the base station. If we set small tunable elements for RIS, we can obtain the best performance. By using MonteCarlo simulation, we verify our analytical results via simulations. Our main results reported in this paper show the positive effect once we deploy RISs for guaranteeing fairness among NOMA users in wireless systems.